2023
DOI: 10.1002/ehf2.14348
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation in elderly patients with acute heart failure: insights from the KCHF registry

Abstract: Aims Several studies demonstrated that tricuspid regurgitation (TR) is associated with poor clinical outcomes. However, data on patients with TR who experienced acute heart failure (AHF) remains scarce. The purpose of this study is to evaluate the association between TR and clinical outcomes in patients admitted with AHF, using a large‐scale Japanese AHF registry. Methods and results The current study population consisted of 3735 hospitalized patients due to AHF in the Kyoto Congestive Heart Failure (KCHF) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Patients with acute decompensated HFpEF patients have a poor 5‐year prognosis with CV causes of half of the mortality cases observed in two thirds after 5 years, for which CAD and tricuspid regurgitation (TR) were predictive factors 27 . In the Japanese Kyoto Congestive Heart Failure (KCHF) registry, increased TR severity was associated with a proportional increase in all‐cause mortality and HF hospitalization 28 . Remarkedly, among 993 patients with moderate/severe TR, the number of patients who underwent surgical intervention for TR within 1 year was only 13 (1.3%) 28 .…”
Section: Valvular Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with acute decompensated HFpEF patients have a poor 5‐year prognosis with CV causes of half of the mortality cases observed in two thirds after 5 years, for which CAD and tricuspid regurgitation (TR) were predictive factors 27 . In the Japanese Kyoto Congestive Heart Failure (KCHF) registry, increased TR severity was associated with a proportional increase in all‐cause mortality and HF hospitalization 28 . Remarkedly, among 993 patients with moderate/severe TR, the number of patients who underwent surgical intervention for TR within 1 year was only 13 (1.3%) 28 .…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…In the Japanese Kyoto Congestive Heart Failure (KCHF) registry, increased TR severity was associated with a proportional increase in all‐cause mortality and HF hospitalization 28 . Remarkedly, among 993 patients with moderate/severe TR, the number of patients who underwent surgical intervention for TR within 1 year was only 13 (1.3%) 28 . To address the optimal timing for tricuspid valve repair, L'Official et al reported a prognostic model for predicting clinical events in patients with isolated functional TR, including right atrial volume index (RAVI) and the tricuspid annular plane systolic excursion to systolic pulmonary arterial pressure (TAPSE/sPAP) ratio for predicting the risk for event at 2 year follow‐up in patients with an isolated functional TR 29 .…”
Section: Valvular Heart Diseasementioning
confidence: 99%